(untitled) (Journal of Scientific Research, 2011)
In the present investigation different fractions (hexane, ethylacetate and methanol) of the whole methanolic extract of Cressa cretica L.(Convolulaceae), a widely grown halophytic plant were studied against wide ranges of bacteria (both positive and negative strain) and five fungi Candida albicans, Candida tropicalis – dimorphic fungi, Aspergillus fumigatus, Aspergillus niger – systemic fungi and fusarium oxysporum by agar disc diffusion method. Among the three fractions the ethylacetate fraction of C.cretica showed the highest activity, but among the pathogens highest activity was revealed against Escherichia coli, Klebsiella pneumoniae (zone of inhibition diameter in mm was found to be 26 and 31, respectively). The ethylacetate fraction was sensitive to both gram +ve and gram –ve bacterias. C.cretica showed higher inhibitory activity against the Aspergillus fumigates, Aspergillus niger (zone of inhibition diameter in mm was found to be 26 and 22, respectively) than the Candida albicans and Candida tropicalis and least was found for Fusarium oxysporum. As ethylacetate fraction revealed better activity than other fractions, further study of morphological and biochemical alterations were carried out only with ethylacetate fraction and the results revealed some morphological and biochemical alterations, which indicates that ethylacetate fraction of C. cretica possess potential broad spectrum antimicrobial activity. Keywords: Cressa cretica; Antifungal; Gram positive bacteria; Gram negative bacteria; Biochemical alterations. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i1.7719 J. Sci. Res. 4 (1), 203-212 (2012)